2007
DOI: 10.1007/s00535-006-1993-9
|View full text |Cite
|
Sign up to set email alerts
|

Possible correlation between iron deposition and enhanced proliferating activity in hepatitis C virus-positive hepatocellular carcinoma in Myanmar (Burma)

Abstract: Possible correlation between iron deposition and enhanced proliferating activity in hepatitis C virus-positive hepatocellular carcinoma in Myanmar (Burma)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In contrast to patients without inherent hemoglobinopathy, ribavirin, that is one of the major determinants of the SVR, can induce life-threatening anemia in thalassemia major patients, and thus, is generally considered contraindicated in these patients [11][12]. In addition to contraindication of ribavirin, high iron content of serum and liver with its probable role in conferring patients’ interferon resistance and its synergistic effect on progression of liver fibrosis is another major confounder in treatment of thalassemia major patients [13][14][15][16][17][18][19]. Previously in a meta-analysis of literature, we showed that peginterferon monotherapy can induce a SVR rate of 28 percent in thalassemia major patients, while combination therapy of peginterferon and ribavirin (low dose therapy, accompanying by tight monitoring of patients) elicits a SVR rate of 44 percent [20].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to patients without inherent hemoglobinopathy, ribavirin, that is one of the major determinants of the SVR, can induce life-threatening anemia in thalassemia major patients, and thus, is generally considered contraindicated in these patients [11][12]. In addition to contraindication of ribavirin, high iron content of serum and liver with its probable role in conferring patients’ interferon resistance and its synergistic effect on progression of liver fibrosis is another major confounder in treatment of thalassemia major patients [13][14][15][16][17][18][19]. Previously in a meta-analysis of literature, we showed that peginterferon monotherapy can induce a SVR rate of 28 percent in thalassemia major patients, while combination therapy of peginterferon and ribavirin (low dose therapy, accompanying by tight monitoring of patients) elicits a SVR rate of 44 percent [20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, apoptosis is involved in several human diseases, including autoimmune diseases, viral hepatitis, hepatocellular carcinoma, ischemia-reperfusion injury (I/R injury), and gastro-intestinal malignancies (1)(2)(3)(4)(5). In the case of liver transplantation, apoptosis in liver allografts was first reported in a porcine model in 1974 (6).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, long-term treatment of patients with chronic HCV infection with iron-reducing agents results in a significant improvement of liver function and marked reduction in the progression to HCC [32,33]. In another study [34], iron deposition was found in 43% of the HCC cases and indicated that, in Myanmar patients with HCC, iron deposition might accelerate hepatocarcinogenesis, by promoting cancer cell proliferation, without affecting the Fas/FasL apoptotic system. A recently study [35] showed that chronic iron overload seemed to induce nuclear localization of MT and NF-jB activation, with a resultant marked acceleration of liver regeneration in ironoverload rats after PH occurring at least 12 h earlier than that in normal-diet rats.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is not yet any evidence to support the correlation of iron deposit in HCC patients with the concentration of iron in groundwater would be indicated in the previous studies. In an excellent work from Soe et al [34] in Japan, Prussian blue staining was performed in order to detect iron deposition, and the iron deposition was found in 43% of the HCC cases. The study showed that, in Myanmar patients with HCC, iron deposition might accelerate hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%